2022
DOI: 10.1021/acs.analchem.2c00303
|View full text |Cite
|
Sign up to set email alerts
|

Nanoprojectile Secondary Ion Mass Spectrometry for Nanometrology of Nanoparticles and Their Interfaces

Abstract: Nanoscale molecular characterization plays a crucial role in enhancing our insights into fundamental and materials processes occurring at the nanoscale. However, for many traditional techniques, measurements on different ensembles are mixed and the analytical result reflects the average surface composition or arrangement. Advances in nanometrologies that allow for measurements to be differentiated based on the chemical environment examined are critical for accurate analysis. Here, we present a variant of secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
(69 reference statements)
0
2
0
Order By: Relevance
“…We next compared the level of surface marker expression in cancer cells and normal EVs. To quantify EV markers, we developed a methodology that uses ions characteristic of the target object or the substrate. , We monitored four colocalized Ab@Ln-tags and determined a relative abundance (%) of each tag which correlates to surface expression of the target protein. As seen from Figure B, the analysis of relative abundance (%) revealed that normal EVs had a higher level of CYP2E1 (hepatic marker) concomitant with lower levels of AFP (liver cancer marker) and EpCAM (generic cancer).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We next compared the level of surface marker expression in cancer cells and normal EVs. To quantify EV markers, we developed a methodology that uses ions characteristic of the target object or the substrate. , We monitored four colocalized Ab@Ln-tags and determined a relative abundance (%) of each tag which correlates to surface expression of the target protein. As seen from Figure B, the analysis of relative abundance (%) revealed that normal EVs had a higher level of CYP2E1 (hepatic marker) concomitant with lower levels of AFP (liver cancer marker) and EpCAM (generic cancer).…”
Section: Resultsmentioning
confidence: 99%
“…Our team has pioneered the SIMS approach whereby a surface is stochastically bombarded with a suite of individual nanoprojectiles (e.g., ∼ 1 keV/atom Au 400 4+ ) in the event-by-event bombardment detection mode. A bombardment event generates a crater of ∼10 nm in diameter within an organic layer on the surface; ionized ejecta from each bombardment event are detected, and mass spectra from millions of such events are compiled. This approach has been used by us previously to examine the heterogeneity of biointerfaces, , thin films, , nanoparticles, and integrated circuits. We have recently demonstrated the feasibility of NP-SIMS for EV analysis using antibodies (Abs)-labeled with halide MS tags and targeting abundant and ubiquitous surface markers, CD63 and CD81 …”
Section: Introductionmentioning
confidence: 99%
“…To quantify EV markers, we developed a methodology that uses ions characteristic of the target object or the substrate. 34,39 We monitored four co-localized Ab@Ln-tags and determined a relative abundance (%) of each tag which correlates to surface expression of the target protein. As seen from Figure 3B, the analysis of relative abundance (%) revealed that normal EVs had a higher level of CYP2E1 (hepatic marker) concomitant with lower levels of AFP (liver cancer marker) and EpCAM (generic cancer).…”
Section: Detecting Individualmentioning
confidence: 99%
“…[30][31][32][33] A bombardment event generates a crater of ~10 nm in diameter within an organic layer on the surface; ionized ejecta from each bombardment event are detected and mass spectra from millions of such events are compiled. This approach has been used by us previously to examine the heterogeneity of biointerfaces, 34,35 thin films, 36,37 nanoparticles, [38][39][40] and integrated circuits. We have recently demonstrated the feasibility of NP-SIMS for EV analysis using antibodies (Abs)-labeled with halide MS tags and targeting abundant and ubiquitous surface markers, CD63 and CD81.…”
Section: Introductionmentioning
confidence: 99%